2021
DOI: 10.15244/pjoes/126236
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fertilizers and Soil Conditioner Recover Chemical Fertilizer-Induced Changes in Soil Bacterial Community Diversity in Wine Grape Rhizosphere Soil

Abstract: Different fertilization strategies can affect the quality of grapes, which in turn affect the taste of wine. This study aimed to investigate the effects of different fertilization treatments on soil fertility and wine grape berry quality, as well as the relationship of soil bacterial diversity and fertilization. Six-year-old Vitis vinifera L. cv. Cabernet Sauvignon plants were randomly planted in 25 test plots with five fertilization treatments: no fertilization, chemical fertilizer, organic fertilizer, combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The effect of fertilizers can be specific to certain bacterial groups [84,85]. The type of fertilizer, whether organic or conventional, can favor the abundance of particular groups of microorganisms while affecting the abundance of others [86], as observed in our results. In the case of humus fertilization, the occurrence of bacterial OTUs increased compared to treatments fertilized with DAP.…”
Section: Discussionsupporting
confidence: 76%
“…The effect of fertilizers can be specific to certain bacterial groups [84,85]. The type of fertilizer, whether organic or conventional, can favor the abundance of particular groups of microorganisms while affecting the abundance of others [86], as observed in our results. In the case of humus fertilization, the occurrence of bacterial OTUs increased compared to treatments fertilized with DAP.…”
Section: Discussionsupporting
confidence: 76%
“…This agrees with previous studies on grapevine microbiome research (Deyett and Rolshausen 2020;Liu et al 2022). Both soils were colonized mainly by Rubrobacter and Gemmatimonadaceae family, which are commonly found bacteria in grapevine soil rhizosphere core microbiome (Wang et al 2021). In sandy soil, plants also contain Vicinamibacterales family in high abundance that are typical of bacterial microbiomes present in soils with high content of sand (Costa et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Bathyarchaeia may play specific roles in regulating ecological functions in different soil environments. Some studies suggested that the improvement of soil fertility by organic fertilizer and soil regulator might decrease the relative abundance of the soil bacterium Steroidobacter ( Wang et al, 2021 ). Steroidobacter was significantly detected in intercropping group in this study and was negatively correlated with a variety of metabolites.…”
Section: Discussionmentioning
confidence: 99%